1998
DOI: 10.1021/cm9705451
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Assemblies of Semiconductor Nanoparticles in Water-Soluble Block Copolymer Aggregates

Abstract: Novel spherical assemblies of CdS-containing block copolymer reverse micelles in aqueous solution have been formed by the slow addition of water to mixtures of the reverse micelles and a polystyrene-b-poly(acrylic acid) stabilizer. The structures are large compound micelles (LCMs) with quantum-confined CdS nanoparticles dispersed throughout a spherical PS matrix, which is stabilized in water by a layer of solubilized hydrophilic chains. The size of the CdS particles (2R CdS ∼ 3 nm) is controlled by the ionic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(131 citation statements)
references
References 27 publications
4
126
1
Order By: Relevance
“…5.2, 4.8, and 4.7 nm were found for the microgels with u 0.11, 0.22, and 0.44, respectively. [13,14] This estimation agreed with the results obtained by image analysis of the TEM images. The reduction in average dimensions of the CdS NPs formed in the poly(NIPAM-AA-HEA) microgels with increase of u indicated that spatial localization of Cd 2+ ions on COO ± groups of PAA hindered nanoparticle growth.…”
Section: Resultssupporting
confidence: 89%
“…5.2, 4.8, and 4.7 nm were found for the microgels with u 0.11, 0.22, and 0.44, respectively. [13,14] This estimation agreed with the results obtained by image analysis of the TEM images. The reduction in average dimensions of the CdS NPs formed in the poly(NIPAM-AA-HEA) microgels with increase of u indicated that spatial localization of Cd 2+ ions on COO ± groups of PAA hindered nanoparticle growth.…”
Section: Resultssupporting
confidence: 89%
“…From the absorption edge (k e ) in their UV-vis spectra, the S-CdS nanoparticles were determined to have diameters of ca. 3, 4, and 7 nm [34,35].…”
Section: Methodsmentioning
confidence: 97%
“…3, 4, and 7 nm. [34][35] The synthesis of the dendritic polyfluorene was performed using a typical Suzuki coupling reaction protocol. The copolymerization of dendritic monomers and 2,7-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-9,9-dioctylfluorene was 16 performed using Pd(PPh 3 ) 4 as a catalyst and Aliquat 336 as a phase-transfer reagent in a mixture of toluene and aqueous potassium carbonate (2.0 M).…”
Section: Methodsmentioning
confidence: 99%